The removal of phenol from aqueous solutions by dehydrated beet pulp carbon - Çiçek, H; Dursun, G (Parlar Scientific Publications (P S P), 2005)
The adsorption of phenol onto dehydrated beet pulp (DBP) was investigated at different initial pHs (1-12), temperatures (25-60 degrees C), and phenol concentrations (25500 mg L-1). The optimum adsorption conditions were found to be 8.0 for initial pH, 100 mg L-1 for initial phenol concentration, 60 degrees C for temperature and 0.5 g L-1 for adsorbent dosage. Adsorption data were well-described by the Freundlich model, although they could also be modelled by Langmuir. The pseudo-first order and pseudo-second order kinetic models were applied to test the experimental data. It was concluded that the pseudo-second order kinetic model provided better correlation of the experimental data rather than the pseudo-first order model. The thermodynamic constants of the adsorption process were also evaluated by using the thermodynamic equilibrium coefficients obtained at different temperatures.
Keywords: phenol; adsorption; dehydrated beet pulp (DBP); equilibrium; kinetic; thermodynamic parameters